Heal : change your mind, change your body, change your life - Noonan Gores, Kelly; Chopra, Deepak; Moorjani, Anita, 1959-; Williamson, Marianne, 1952-; Beckwith, Michael; Lipton, Bruce H.; Dispenza, Joe, 1962-; Mascara, Tina; Hamilton, David; Borysenko, Joan; Braden, Gregg; Williams, Anthony; et al. ([United States] : 1091 Media, 2017)
A documentary film that takes us on a scientific and spiritual journey where we discover that by changing one's perceptions, beliefs, and emotions, the human body can heal itself from any disease.
Directed by Kelly Noonan Gores.
Featuring Dr. Deepak Chopra, Anita Moorjani, Marianne Williamson, Dr. Michael Beckwith, Dr. Bruce Lipton, Dr. Joe Dispenza, Anthony William, Gregg Braden, Dr. Joan Borysenko, Dr. David Hamilton, Dr. Kelly Brogan, Rob Wergin, Dr. Kellly Turner, Peter Crone, Dr. Darren Weissman, and Dr. Jeffrey Thompson.
Rated R.
Mode of access: World Wide Web.
Keywords: Mind and body therapies; Healing; Meditation; Video recordings for the hearing impaired